Pengenalan Aplikasi Phet Simulation Sebagai Media Pembelajaran Untuk Materi Konsep Getaran di SMA Teruna Bakti Waena Jayapura - Ngaderman, Hubertus; Ego Srivajawaty Sinaga; Papilaya, Eva; Truly Theresia Saputrina (Universitas Sulawesi Barat, 2022)
The task of a lecturer is to carry out the Tri Dharma of Higher Education, one of which is to do community service. Service activities have been carried out on the fourth week of April 2022 which is located at SMA taruna Bakti Waena Jayapura, the number of students who attended were 28 students and were accompanied by one of the teachers who taught Physics. The material presented was about the introduction of PhET Simulation Application as learning media for Masses and Springs. The goal to be achieved from this activity is so that students get enlightenment about the concept of Masses and Springs through the PhET Simulation application. The method used is lecture, question and answer, demonstration. The results obtained before using the PhET Simulation application, students had little difficulty understanding the concept of Masses and Springs, but after using the application, students understood the concept of Masses and Springs.